2019
DOI: 10.1002/btm2.10137
|View full text |Cite
|
Sign up to set email alerts
|

Understanding optical reflectance contrast for real‐time characterization of epithelial precursor lesions

Abstract: Detecting early‐stage epithelial cancers and their precursor lesions are challenging as lesions could be subtle and focally or heterogeneously distributed over large mucosal areas. Optical coherence tomography (OCT) that enables wide‐field imaging of subsurface microstructures in vivo is a promising screening tool for epithelial diseases. However, its diagnostic capability has not been fully appreciated since the optical reflectance contrast is poorly understood. We investigated the back‐scattered intensities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The µOCT technology has been described previously 113 116 . In brief, the µOCT system included a Spectral-domain OCT (SD-OCT) imaging console and a benchtop probe.…”
Section: Methodsmentioning
confidence: 99%
“…The µOCT technology has been described previously 113 116 . In brief, the µOCT system included a Spectral-domain OCT (SD-OCT) imaging console and a benchtop probe.…”
Section: Methodsmentioning
confidence: 99%
“…Here the pixel‐resolution rescale operations were performed on the 3D image volumes, and a specific index mentioned in Section 2.3 was chosen to numerically rescale the axial pixel resolution to achieve that the acquired 3D image volumes have the same pixel resolution along different axis directions, so it can be more convenient to observe and measure the 3D morphology of human placental villi. Meanwhile, here we assumed the refractive index of the sample over a wide range of wavelengths as ~1.38, following the References 30 , 31 to estimate the OCT axial optical resolution in the sample, which was ~1.7 μm.…”
Section: Discussionmentioning
confidence: 99%
“…μOCT, a cellular-resolution OCT system, provides the real-time cross-sectional images of tissues with a spatial resolution of 1-2 μm which is around one order of magnitude higher than the standard OCT technology. Previous studies have demonstrated its capability to recognize subcellular structures underneath the surface in tissues like atherosclerotic coronary artery wall [7], oral mucosa and esophageal mucosa [19]. To uncover the scattering characteristics of basement membrane underlying the epithelium, in this study we simulated the scattering feature of basement membrane numerically and validated the simulation results in human oral and esophageal mucosa experimentally using μOCT.…”
Section: Introductionmentioning
confidence: 93%
“…A previously developed µOCT system was used in this study [19,20]. Briefly, the light went to reference arm and sample arm respectively after being divided by a beam splitter (PAFA-X-4-B, Thorlabs, New York).…”
Section: µOct Imaging Systemmentioning
confidence: 99%